2010
DOI: 10.4310/jdg/1279114299
|View full text |Cite
|
Sign up to set email alerts
|

Calabi flow and projective embeddings

Abstract: Let X ⊂ CP N be a smooth subvariety. We study a flow, called balancing flow, on the space of projectively equivalent embeddings of X which attempts to deform the given embedding into a balanced one. If L → X is an ample line bundle, considering embeddings via H 0 (L k ) gives a sequence of balancing flows. We prove that, provided these flows are started at appropriate points, they converge to Calabi flow for as long as it exists. This result is the parabolic analogue of Donaldson's theorem relating balanced em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 34 publications
1
61
0
Order By: Relevance
“…More generally, if M is any complex manifold and (q) k has O(k −n 0 ) small spectral gap on an open set D ⋐ M (see Definition 1.5 in [9], for the precise meaning of O(k −n 0 ) small spectral gap), then it is known by a recent result (see Theorem 1.6 in [9]) that the Bergman kernel admits a full asymptotic expansion in k on D. The coefficients of these expansions turned out to be deeply related to various problem in complex geometry (see e.g. [3], [4], [5]). …”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, if M is any complex manifold and (q) k has O(k −n 0 ) small spectral gap on an open set D ⋐ M (see Definition 1.5 in [9], for the precise meaning of O(k −n 0 ) small spectral gap), then it is known by a recent result (see Theorem 1.6 in [9]) that the Bergman kernel admits a full asymptotic expansion in k on D. The coefficients of these expansions turned out to be deeply related to various problem in complex geometry (see e.g. [3], [4], [5]). …”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Now the formal adjoint of ∂ s for the inner product ( | ) given by (1.4) is 4) where in view of the unitarity of the relation (3.1),…”
Section: 1the Transport Equationsmentioning
confidence: 99%
“…Proof The proof is already contained in [10,Appendix] and [14] where the case of E trivial is treated in details. The important point is that the full Bergman kernel expansion holds in our setting, see [4,Theorem 4.18'].…”
Section: Moreover (3) Is Uniform In the Sense That There Is An Integmentioning
confidence: 99%
“…Donaldson in the study of the constant scalar curvature problem for Kähler metrics, in relation with the socalled Yau-Tian-Donaldson conjecture, see [7]. In [10], Fine introduced another balancing flow that approximates the Calabi flow, a 4th order parabolic PDE that is expected to deforms a given Kähler metric towards a constant scalar curvature one. In [3] it was introduced the Ω-balancing flow and shown that it converges towards a flow of Kähler metrics that enjoys similar properties to the Kähler-Ricci flow, providing a new approach to the classical Calabi conjecture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation